Investigation of hepatitis A outbreak in district of Manjung, Perak, Malaysia, October 2012 - Yusoff, Faudzi Ahmad; Rahman, Rusdi Abdul; Ling, He Mey; Budart, Suzana; Sulaiman, Lokman Hakim (Western Pacific Surveillance and Response, 2015)
Background: In September 2012, ten cases suspected to be Hepatitis A were notified to the Manjung District Health Department, the number of cases increased by time and outbreak was declared. An investigation was conducted to identify the possible mode of transmission, source of outbreak and to recommend implementable preventive and control measures. Methods: We defined a case as an acute illness with a discrete onset of symptoms and jaundice or elevated serum aminotransferase levels, in September 2012 at Manjung District. We reviewed all cases and designed a community-based case-control study including environmental assessment. Logistic regression analysis was performed. Results: The date of onset for the index case was on 8 September 2012. There were 78 cases confirmed as hepatitis A. The attack rate was 3.1 per 10,000 population. Sub-District Ayer Tawar showed highest incidence (47.4%). Majority of the cases occurred among Indians (5.1 per 1000 population), active age groups (25-40 years), low income and working as labourer. Using epidemic curve, the possible time of exposure was between 14th -25th August 2012, (33rd to 34th of Epidemiological weeks). Multiple logistic regression showed male [OR: 18.4 (5.13-65.9), p<0.001], and those who drank toddy at Sitiawan [OR: 2.70 (1.17-6.25), (p< 0.05)] were statistically significant. Conclusion: Toddy was possible to be a primary source of outbreak. Male and those who consumed Toddy at Sitiawan were at a higher risk of getting the infection. We recommended a temporary closure of Toddy preparation place and weekly follow up on the cases. Keywords: hepatitis A, outbreaks, toddy Corresponding Author: Ahmad Faudzi Yusoff, Unit of Epidemiology, Medical Research Resource Centre, Institute for Medical Research, Jalan Pahang 50588 Kuala Lumpur, Malaysia Email: faudzi@imr.gov.my